Beta‐blockers and inhibitors of the renin‐angiotensin aldosterone system for chronic heart failure with preserved ejection fraction - Martin, Nicole (Cochrane Database Syst Rev, 2018)
BACKGROUND: Beta‐blockers and inhibitors of the renin‐angiotensin aldosterone system improve survival and reduce morbidity in people with heart failure with reduced left ventricular ejection fraction. There is uncertainty whether these treatments are beneficial for people with heart failure with preserved ejection fraction and a comprehensive review of the evidence is required. OBJECTIVES: To assess the effects of beta‐blockers, angiotensin converting enzyme inhibitors, angiotensin receptor blockers, angiotensin receptor neprilysin inhibitors, and mineralocorticoid receptor antagonists in people with heart failure with preserved ejection fraction. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase and two clinical trial registries on 25 July 2017 to identify eligible studies. Reference lists from primary studies and review articles were checked for additional studies. There were no language or date restrictions. SELECTION CRITERIA: We included randomised controlled trials with a parallel group design enrolling adult participants with heart failure with preserved ejection fraction, defined by a left ventricular ejection fraction of greater than 40 percent. DATA COLLECTION AND ANALYSIS: Two review authors independently selected studies for inclusion and extracted data. The outcomes assessed included cardiovascular mortality, heart failure hospitalisation, hyperkalaemia, all‐cause mortality and quality of life. Risk ratios (RR) and, where possible, hazard ratios (HR) were calculated for dichotomous outcomes. For continuous data, mean difference (MD) or standardised mean difference (SMD) were calculated. We contacted trialists where neccessary to obtain missing data. MAIN RESULTS: 37 randomised controlled trials (207 reports) were included across all comparisons with a total of 18,311 participants. Ten studies (3087 participants) investigating beta‐blockers (BB) were included. A pooled analysis indicated a reduction in cardiovascular mortality (15% of participants in the intervention arm versus 19% in the control arm; RR 0.78; 95% confidence interval (CI) 0.62 to 0.99; number needed to treat to benefit (NNTB) 25; 1046 participants; 3 studies). However, the quality of evidence was low and no effect on cardiovascular mortality was observed when the analysis was limited to studies with a low risk of bias (RR 0.81; 95% CI 0.50 to 1.29; 643 participants; 1 study). There was no effect on all‐cause mortality, heart failure hospitalisation or quality of life measures, however there is uncertainty about these effects given the limited evidence available. 12 studies (4408 participants) investigating mineralocorticoid receptor antagonists (MRA) were included with the quality of evidence assessed as moderate. MRA treatment reduced heart failure hospitalisation (11% of participants in the intervention arm versus 14% in the control arm; RR 0.82; 95% CI 0.69 to 0.98; NNTB 41; 3714 participants; 3 studies; moderate‐quality evidence) however, little or no effect on all‐cause and cardiovascular mortality and quality of life measures was observed. MRA treatment was associated with a greater risk of hyperkalaemia (16% of participants in the intervention group versus 8% in the control group; RR 2.11; 95% CI 1.77 to 2.51; 4291 participants; 6 studies; high‐quality evidence). Eight studies (2061 participants) investigating angiotensin converting enzyme inhibitors (ACEI) were included with the overall quality of evidence assessed as moderate. The evidence suggested that ACEI treatment likely has little or no effect on cardiovascular mortality, all‐cause mortality, heart failure hospitalisation, or quality of life. Data for the effect of ACEI on hyperkalaemia were only available from one of the included studies. Eight studies (8755 participants) investigating angiotensin receptor blockers (ARB) were included with the overall quality of evidence assessed as high. The evidence suggested that treatment with ARB has little or no effect on cardiovascular mortality, all‐cause mortality, heart failure hospitalisation, or quality of life. ARB was associated with an increased risk of hyperkalaemia (0.9% of participants in the intervention group versus 0.5% in the control group; RR 1.88; 95% CI 1.07 to 3.33; 7148 participants; 2 studies; high‐quality evidence). We identified a single ongoing placebo‐controlled study investigating the effect of angiotensin receptor neprilysin inhibitors (ARNI) in people with heart failure with preserved ejection fraction. AUTHORS' CONCLUSIONS: There is evidence that MRA treatment reduces heart failure hospitalisation in heart failure with preserverd ejection fraction, however the effects on mortality related outcomes and quality of life remain unclear. The available evidence for beta‐blockers, ACEI, ARB and ARNI is limited and it remains uncertain whether these treatments have a role in the treatment of HFpEF in the absence of an alternative indication for their use. This comprehensive review highlights a persistent gap in the evidence that is currently being addressed through several large ongoing clinical trials.